Going Beyond Rate Changes as the Sole Indicator for Dynamic Triggering of Earthquakes - Pankow, Kristine L. (Sci Rep, 2020)
Remote earthquake triggering is a well-established phenomenon. Triggering is commonly identified from statistically significant increases in earthquake rate coincident with the passage of seismic energy. In establishing rate changes, short duration earthquake catalogs are commonly used, and triggered sequences are not typically analyzed within the context of background seismic activity. Using 500 mainshocks and four western USA 33-yearlong earthquake catalogs, we compare the ability of three different statistical methods to identify remote earthquake triggering. Counter to many prior studies, we find remote dynamic triggering is rare (conservatively, <2% of the time). For the mainshocks associated with remote rate increases, the spatial and temporal signatures of triggering differ. We find that a rate increase coincident in time with mainshock energy alone is insufficient to conclude that dynamic triggering occurred. To classify dynamically triggered sequences, we suggest moving away from strict statistical measurements and instead use a compatibility assessment that includes multiple factors, like spatial and temporal indicators.